3+2*A+B*4/2-4 = 3 + 2A + 2B - 4 = 2A + 2B - 1
It is a linear expression with one variable, b. Since it is not an equation it cannot be solved.
You need values for a and b, then you multiply a by 3, b by 2 and add your answers.
If you mean: -3*(-2b-3)+7b then it is an algebraic expression that can be simplified to 6b+9+7b = 13b+9
It is a numerical expression.
(a2 + 2)(b + 3)
8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3
It is an equation and the value of b is 3
2B Multiplied by 3 plus B = 7B. Here is how it's worked out. You start with 2B, multiply that by 3 and you get 6B. Now all you have to do is add the last B, therefore adding 1B to equal 7B.